Pengaruh Antusiasme Belajar dan Media Belajar Website “Sekolah Digital SMKN 3 Salatiga” Terhadap Prestasi Belajar Simulasi Digital - Yehoshua Yohan Ary Anando; Adriyanto Juliastomo Gundo (Jurnal Ilmiah Wahana Pendidikan, 2022)
Online learning is a solution to carry out learning during the COVID-19 pandemic. To support the implementation of online learning methods, learning enthusiasm and learning media on the "Digital School SMKN 3 Salatiga" website are needed to be able to maintain and improve students' digital simulation learning achievement. The purpose of this study was to see how the influence of learning enthusiasm and learning media on the website "Digital School of SMKN 3 Salatiga" on digital simulation learning achievement at SMKN 3 Salatiga simultaneously or partially. This research is quantitative in nature using a descriptive survey method through regression analysis involving 100 samples of students. The results showed that learning enthusiasm and learning media on the website "Digital School SMKN 3 Salatiga" had a level of influence of 0.107 or 10.7%, although it only had a small effect but had a positive and significant effect on digital simulation learning achievement.